2016
DOI: 10.1111/acel.12451
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat composition influences glomerular and proximal convoluted tubule cell structure and autophagic processes in kidneys from calorie-restricted mice

Abstract: SummaryCalorie restriction (CR) has been repeatedly shown to prevent cancer, diabetes, hypertension, and other age‐related diseases in a wide range of animals, including non‐human primates and humans. In rodents, CR also increases lifespan and is a powerful tool for studying the aging process. Recently, it has been reported in mice that dietary fat plays an important role in determining lifespan extension with 40% CR. In these conditions, animals fed lard as dietary fat showed an increased longevity compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The age-related changes in the kidney can also be modulated by caloric restriction. In calorie-restricted animals, age-associated structural and functional changes in the kidney were mitigated and animals were resistant to diverse experimental kidney injuries ( Calvo-Rubio et al, 2016 ). In humans, life-long caloric restriction is not feasible, but the beneficial effects of even short-term calorie restriction have been unequivocally demonstrated, including reduced blood pressure, body weight, blood cholesterol, blood glucose, and attenuated atherosclerosis, as well as a decrease in blood urea nitrogen, creatinine, and uric acid ( Walford et al, 2002 ).…”
Section: Therapeutic Strategies For Renal Ageingmentioning
confidence: 99%
“…The age-related changes in the kidney can also be modulated by caloric restriction. In calorie-restricted animals, age-associated structural and functional changes in the kidney were mitigated and animals were resistant to diverse experimental kidney injuries ( Calvo-Rubio et al, 2016 ). In humans, life-long caloric restriction is not feasible, but the beneficial effects of even short-term calorie restriction have been unequivocally demonstrated, including reduced blood pressure, body weight, blood cholesterol, blood glucose, and attenuated atherosclerosis, as well as a decrease in blood urea nitrogen, creatinine, and uric acid ( Walford et al, 2002 ).…”
Section: Therapeutic Strategies For Renal Ageingmentioning
confidence: 99%
“…78,80,81 For the kidney, it has been shown that calorie restriction counteracts basically all age-associated changes including glomerulosclerosis, tubular atrophy, and interstitial fibrosis. 9,34,[82][83][84] In addition to examination of its role in calorie restriction, autophagy has been intensively studied in aging and in different disease models in the kidney. 85 It was suggested that because of their longevity, podocytes, as well as tubular cells, might be particularly dependent on autophagy for effective "self-cleaning" from protein aggregates and defective organelles during the lifespan.…”
Section: Structural and Functional Changes Of Kidney Cellsmentioning
confidence: 99%
“…In this review, we have introduced the renal benefits of calorie restriction. 9,34,[82][83][84]131 However, long-term calorie restriction with optimal nutrition is very difficult to achieve and unlikely to become clinically relevant in the near future. Several nutritional factors and small compounds mimicking the calorie restriction effects by regulating nutrient sensing pathways or by inducing autophagy are in different phases of preclinical and clinical testing.…”
Section: Therapeutic Potentialmentioning
confidence: 99%
“…For example, kidney aging indicators such as glomerular enlargement, podocyte hypertrophy, and mitochondrial abnormality have been delayed or even reversed by CR [ 7 , 8 ]. Similarly, other researchers have shown that CR attenuates most of the analyzed age-related markers in kidney, such as glomerular basement membrane (GBM) thickness, mitochondrial mass in complex proximal tubules and autophagic markers in aged kidney [ 9 ]. Furthermore, CR has been shown to decrease age-associated renal fibrosis and chronic kidney diseases [ 10 ].…”
Section: Introductionmentioning
confidence: 98%